Urgensi Pendidikan Islam Dalam Peradilan Pidana Anak Berdasarkan Undang-Undang No. 11 Tahun 2012 - Purba, Julhaidir; Albani Nasution, Muhammad Syukri; Pulungan, Sahmiar (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research focuses on the importance of strengthening Islamic education in juvenile criminal justice by reviewing Law No.11/2012. The juvenile justice system in Indonesia through Law No. 11/2012 is very important to see the importance of strengthening children's character through Islamic education. The background of this research is the need for protection and guidance of children through education, especially in an effort to keep children away from criminal acts, thus ensuring behavior that suits their needs. The research method is juridical sociological, combining normative analysis of legislation with its application in the social context. The results of this study confirm the importance of Islamic education in strengthening children's character based on Law No. 11/2012 on Juvenile Justice in the context of Indonesian law, taking into account the principles of Islamic Law. The findings reflect the need to strengthen children's Islamic education through formal and informal institutions that focus more on the special needs of children, including protection and guidance, as well as the importance of the role of parents. This research shows that the implementation of this law still faces challenges, especially in terms of the availability of educational facilities and adequate human resources to deal with children in conflict with the law.